2002
DOI: 10.1111/j.1651-2227.2002.tb01643.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary exercise parameters in children with atrial septal defect and increased pulmonary blood flow: short‐term effects of defect closure

Abstract: Markedly increased pulmonary blood flow because of a relevant atrial septal defect (ASD) leads to impaired cardiopulmonary function during maximum exercise in adults. No comparative preoperative and postoperative data are available on the short‐term effects of shunt closure on cardiorespiratory function at peak exercise in children. Pulmonary function testing at rest and cardiopulmonary exercise testing together with haemodynamic assessment was done prospectively in children with an ASD preoperatively and agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Although exercise capacity seems to insidiously decrease with age, serial CPET studies starting from paediatric age are clearly missing (24). In a small paediatric cohort (N=16), CPET parameters in children with ASD only slightly differ from those in normal children (71). Another small cohort (N=10) found no differences in terms of VO 2max between children with ASD and controls (72).…”
Section: Cpet In Paediatric Patients With Asdsmentioning
confidence: 98%
“…Although exercise capacity seems to insidiously decrease with age, serial CPET studies starting from paediatric age are clearly missing (24). In a small paediatric cohort (N=16), CPET parameters in children with ASD only slightly differ from those in normal children (71). Another small cohort (N=10) found no differences in terms of VO 2max between children with ASD and controls (72).…”
Section: Cpet In Paediatric Patients With Asdsmentioning
confidence: 98%
“…Several studies have reported the short- and long-term effects of ASD closure on patients and many of them demonstrate improved cardiopulmonary function [812], even in patients with a relatively small shunt ratio [13]. However, other studies have either shown no improvement in exercise capacity following defect closure [14, 15] or impaired exercise response compared to healthy controls [16, 17]. Therefore, better understanding of which patients will benefit from closure of ASD is of value.…”
Section: Introductionmentioning
confidence: 99%
“…12,24 In our study, significantly diminished exercise capacity as indicated by lower peak VO 2 assessed by graded symptom-limited exercise testing was found in ASD children, either in surgically closed, transcatheter closure, or unrepaired status. In previous studies, ASD patients have impaired exercise capacity and declined peak VO 2 that is often at 50% to 60% of predicted values in healthy controls 12,[25][26][27] ; even in asymptomatic patients having minor reduction in peak oxygen consumption. 28 Besides, other CPET parameters including VE/VCO 2 slope, MET or VO 2 at AT, RER, pulse oximetry, VE/VO 2 , and VE/CO 2 are considered abnormal among ASD patients.…”
Section: Discussionmentioning
confidence: 88%